Shocking the surreal world of Elsa Schiaparelli - Carron de la Carrière, Marie-Sophie; Carron de la Carrière, Marie-Sophie; Schiaparelli, Elsa 1890-1973; Schiaparelli, Elsa 1890-1973 (Thames & Hudson, 2022)
The couturiere Elsa Schiaparelli (1890-1973) was a key figure in Paris fashion between the two World Wars. Following in the footsteps of her mentor Paul Poiret, she designed her first knitwear collection in January 1927. Decorated with trompe-l'oeil motifs in black and white, her sweaters were an immediate success in both France and the USA. In 1935, the Maison Schiaparelli opened in the Place Vendome in Paris, selling collections designed for sports, city and evening wear.00Like her arch-rival Gabrielle Chanel, Schiaparelli also worked closely with artists, including Man Ray, Jean Cocteau and Salvador Dali, with whom she created a lobster dress. Taking a cue from Surrealism, her creations were hugely imaginative and made use of innovative new materials. The 'Schiap' style continued to develop through the 1930s. Her most famous collections had themes including the circus (summer 1938) and astrology (winter 1938-39). In 1937, Schiaparelli launched the fragrance Shocking, named after shocking pink, which had become her signature colour.00Alongside vintage photographs, sketches and contemporary features from Harper's Bazaar and Vogue, this volume presents specially photographed masterpieces from the collection of the Musee des Arts Decoratifs in Paris. All 120 garments and accessories from the Schiaparelli archive are illustrated, along with a selection of her drawings dating from 1933 to 1953.00Exhibition: Musée des Arts Décoratifs, Paris, France (06.07.2022 - 22.01.2023).00French catalogue ISBN 9782383140009 (Paris: Les Arts Décoratifs, 2022)
Keywords: Schiaparelli, Elsa -- 1890-1973; Ausstellungskatalog -- Musée des Arts Décoratifs -- Paris; Bildband